Conductance Mechanisms of Rapidly Desensitizing Cation Channelrhodopsins from Cryptophyte Algae - Oleg A. Sineshchekov; Elena G. Govorunova; Hai Li; Yumei Wang; Michael Melkonian; Gane K.-S. Wong; Leonid S. Brown; John L. Spudich (mBio, 2020)
ABSTRACT Channelrhodopsins guide algal phototaxis and are widely used as optogenetic probes for control of membrane potential with light. “Bacteriorhodopsin-like” cation channelrhodopsins (BCCRs) from cryptophytes differ in primary structure from other CCRs, lacking usual residues important for their cation conductance. Instead, the sequences of BCCR match more closely those of rhodopsin proton pumps, containing residues responsible for critical proton transfer reactions. We report 19 new BCCRs which, together with the earlier 6 known members of this family, form three branches (subfamilies) of a phylogenetic tree. Here, we show that the conductance mechanisms in two subfamilies differ with respect to involvement of the homolog of the proton donor in rhodopsin pumps. Two BCCRs from the genus Rhodomonas generate photocurrents that rapidly desensitize under continuous illumination. Using a combination of patch clamp electrophysiology, absorption, Raman spectroscopy, and flash photolysis, we found that the desensitization is due to rapid accumulation of a long-lived nonconducting intermediate of the photocycle with unusually blue-shifted absorption with a maximum at 330 nm. These observations reveal diversity within the BCCR family and contribute to deeper understanding of their independently evolved cation channel function. IMPORTANCE Cation channelrhodopsins, light-gated channels from flagellate green algae, are extensively used as optogenetic photoactivators of neurons in research and recently have progressed to clinical trials for vision restoration. However, the molecular mechanisms of their photoactivation remain poorly understood. We recently identified cryptophyte cation channelrhodopsins, structurally different from those of green algae, which have separately evolved to converge on light-gated cation conductance. This study reveals diversity within this new protein family and describes a subclade with unusually rapid desensitization that results in short transient photocurrents in continuous light. Such transient currents have not been observed in the green algae channelrhodopsins and are potentially useful in optogenetic protocols. Kinetic UV-visible (UV-vis) spectroscopy and photoelectrophysiology reveal that the desensitization is caused by rapid accumulation of a nonconductive photointermediate in the photochemical reaction cycle. The absorption maximum of the intermediate is 330 nm, the shortest wavelength reported in any rhodopsin, indicating a novel chromophore structure.